2021
DOI: 10.1177/09544070211014290
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue level detection using multivariate autoregressive exogenous nonlinear modeling based on driver body pressure distribution

Abstract: Prolonged driving causes symptoms of fatigue in drivers and changes their physical condition during driving. The purpose of this paper is to use a force measurement system located in the driver’s seat by force-sensitive resistance pressure sensors in order to record the received information to predict fatigue by learning regression-based models. This system is designed with 16 FSR (Force Sensing Resistor) sensors mounted on the seat and its backrest that records the driver’s body’s data, based on the force exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although the recognition rate was 88.3%, the study lays the foundation for applicable fatigue detection systems. Another more readily applicable method is the one developed by Parsa et al (2021), which uses pressure sensors placed on the seat and the backrest of the driver. The fatigue index of the system is divided in five parts and the driver is considered to be tired when they have crossed 75% of the fatigue index.…”
Section: Literature Relevant To Fatigue and Drowsiness Detectionmentioning
confidence: 99%
“…Although the recognition rate was 88.3%, the study lays the foundation for applicable fatigue detection systems. Another more readily applicable method is the one developed by Parsa et al (2021), which uses pressure sensors placed on the seat and the backrest of the driver. The fatigue index of the system is divided in five parts and the driver is considered to be tired when they have crossed 75% of the fatigue index.…”
Section: Literature Relevant To Fatigue and Drowsiness Detectionmentioning
confidence: 99%
“…Previous studies [16,17,20,21] reported that it is theoretically possible to estimate driver distraction and fatigue levels by measuring body pressure distribution to detect driver posture and behavior. Driver posture was reported to be correlated with driving comfort, and a decrease in comfort could result in driver distraction [17].…”
Section: Introductionmentioning
confidence: 99%